Translation Techniques of Islamic Terminologies in Bilingual Children Story Books - Shafa Firda Nila; Yollanda Octavitri (JURNAL ARBITRER, 2020)
The current research focuses on analyzing the translation techniques of Islamic terminologies in bilingual children storybooks from Indonesian into English. The source of the data is two selected bilingual children storybooks Seri Belajar Islam sejak Usia Dini. This study applied a descriptive qualitative approach to analyze the data, to explain the phenomena, and to withdraw the conclusion. The result showes that in Ayo Belajar Manasik Haji there are 33 Islamic terminologies and 6 translation techniques, while in Ayo Belajar Hadist there are 24 Islamic terminologies and 5 translation techniques.